(untitled) (Global Journal of Management and Business Research, 2015)
This study offers a pioneering description of non-conventional organizations (NCOs), enterprises which the authors suggest provide potential templates for the structure and operation of organizations of the future. Using established definitions of what constitutes an entrepreneur, the authors establish two criteria by which an organization might be judged as being an NCO, including the notion of "absolute uniqueness" and, according to the evolutionary model, the ability to pass on their non-conventional solutions to organizations of the future. The authors identify NCOs of the past and propose candidate NCOs of the present.